Report on 4 Diastasic Perforations of Cecum by Distal Colonic Cancers in occlusion, Treated by Primary Colectomy - Estefan, Alberto; Delgado, Bolívar; Pignata, Daniel (Cirugía del Uruguay, 1979)
Report on 4 cases, treated personally by the authors, of diastasic cecum perforation by distal colonic cancers in occlusion, treated by col'ectomy as acute cases·. There were no postoperatory deaths.